Antipsychotic-induced weight gain and birth weight in psychosis: A fetal programming model. (August 2019) - Garriga, Marina; Fernandez-Egea, Emilio; Mallorqui, Andrea; Serrano, Lourdes; Oliveira, Cristina; Parellada, Eduard; Kirkpatrick, Brian; Vieta, Eduard; Bernardo, Miquel; Garcia-Rizo, Clemente
Abstract: Antipsychotic induced weight gain is a frequent reason for treatment discontinuation in psychosis, subsequently increasing the risk of relapse and negatively affecting patient well-being. The metabolic effect of weight gain and the subsequent risk of obesity constitute a major medical problem on the long term. Despite its consequences, to date few risk factors have been identified (age, gender, body mass index at baseline), with some authors suggesting the implication of early life stressful events, such as perinatal conditions. We aim to describe if a surrogate marker of intrauterine environment (birth weight) might predict weight gain in a cohort of 23 antipsychotic naïve patients at the onset of the psychotic disease evaluated during 16 weeks with olanzapine treatment and in another cohort of 24 psychosis-resistant patients initiating clozapine assessed for 18 weeks. Two independent linear mixed model analyses were performed in each cohort of patients, with prospective weight gain as the dependent variable, age, gender, body mass index, duration of treatment and time as independent variables. Only in naïve patients, weight gain due to antipsychotics was significantly associated with birth weight, while male gender and body mass index at baseline were associated in both cohorts of patients. Treatment-resistant psychotic patients under clozapine were older, had previous antipsychotic treatment and more years of disease, confounders that might have influence a non significant association. Our results suggest that early environmental events might be playing a role in weight evolution in naïve patients treated with antipsychotics.